Debi Cornwall : Necessary Fictions. (Santa Fe : Radius Books, 2020)
Necessary Fictions is a book and multimedia installation exploring American "state-created realities." What are stories we are told, the games we play, to manage unsettling realities? How are fictions deployed and embraced, and to what end? What happens to a society that cannot discern fantasy from reality? (provided by publisher)
boek
Keywords: Cornwall, Debi